2015
DOI: 10.2110/jsr.2015.16
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Estimation of the Position of An Apex: Application To the Geological Record

Abstract: Knowing the position of an apex of a distributive depositional system can provide important spatial constraints on paleogeographic reconstructions, and thus can greatly help facies predictions, at both a system and a basin scale. To date, predicting the position of an apex of a sedimentary system is often limited to generalized statements based on facies mapping and qualitative analyses of paleocurrent readings. This paper presents a user-friendly quantitative methodology based on the von Mises distribution an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 34 publications
2
20
1
Order By: Relevance
“…Paleocurrent data presented in this study (Fig. 1) and Owen et al (2015) do not support this inasmuch as paleoflow is shown to be going east towards the ancestral Rockies, as opposed to west and away from them. A petrographic analysis conducted by Owen (2014) also discounts this view, in that a change in composition was not found.…”
contrasting
confidence: 71%
See 2 more Smart Citations
“…Paleocurrent data presented in this study (Fig. 1) and Owen et al (2015) do not support this inasmuch as paleoflow is shown to be going east towards the ancestral Rockies, as opposed to west and away from them. A petrographic analysis conducted by Owen (2014) also discounts this view, in that a change in composition was not found.…”
contrasting
confidence: 71%
“…1; Owen et al 2015). Owen et al (2015) use a methodology based on the von Mises distribution and the method of maximum likelihood to obtain an estimated apex and associated confidence regions for the system. The authors determined that the apex of this DFS was located in northeastern Arizona (Fig.…”
Section: Salt Wash Dfsmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, the river system trends parallel to the sides of the basin and no radial pattern is 1083 developed. Thus, the width of the sedimentary basin relative to the river size and orientation may have 1084 some control on whether a DFS can develop (Hartley et al, 2010b from an apex that is statistically estimated to be located in northwestern Arizona (Owen et al 2015a). 1115…”
Section: Large Rivers and Theirpreservationpotential 946mentioning
confidence: 99%
“…The succession is interpreted to represent a large DFS that flowed in a north to northeast direction ( Fig. 1; Craig et al, 1956;Mullens and Freeman, 1957;Owen et al, 2015aOwen et al, , 2015b. The system comprises large-scale amalgamated channel belt deposits that can extend tens of kilometers laterally in the proximal region.…”
Section: Study Areamentioning
confidence: 99%